2011
DOI: 10.4161/hv.7.1.13949
|View full text |Cite
|
Sign up to set email alerts
|

Second National Immunization Congress 2010: Addressing vaccine financing for the future in the US

Abstract: At the 2nd National Immunization Congress held in Chicago, IL, from August 31-September 2, 2010, partners from government, provider groups, academia, and manufacturers gathered to discuss the progress made and the future of financing child, adolescent, and adult vaccines. The meeting is a continuation of a solution-oriented vaccine financing dialogue held in February 2007 at the 1st Immunization Congress. The need for this forum arose from concerns that increased costs of immunization could hinder the ability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…The Infectious Diseases Society of America has suggested that the Centers for Medicare and Medicaid Services (CMS) should work to assure physician billing codes adequately cover the full costs of providing immunizations 42,43 and to do this CMS may require updated information about how much it actually costs to immunize an adult. 2 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Infectious Diseases Society of America has suggested that the Centers for Medicare and Medicaid Services (CMS) should work to assure physician billing codes adequately cover the full costs of providing immunizations 42,43 and to do this CMS may require updated information about how much it actually costs to immunize an adult. 2 …”
Section: Discussionmentioning
confidence: 99%
“…1 National stakeholders in adult immunization have voiced concerns about gaps in financing for adult vaccines 2 being one source of the problem and prior research 3,4 suggests physicians view financial barriers as key contributors to low adult immunization rates. Comparatively, the U.S. pediatric vaccination program has been much more successful 5 and benefits from the financial infrastructure of the Vaccines for Children program (VFC).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 In 2010, the Second National Immunization Congress was convened with the goal of addressing future vaccine financing for the United States, with additional focus on adult immunization infrastructure barriers and access challenges. 12 Identifying community immunizers who can supplement the role of primary care providers (PCPs) becomes pertinent given that immunization recommendations will expand over the coming years, while primary care is already reeling under present service demands and cost containment. 13 Currently, more than 170,000 pharmacists in the United States have been trained to provide immunizations, primarily through the nationally recognized certificate training program provided by the American Pharmacist Association.…”
Section: What This Study Addsmentioning
confidence: 99%
“…However, increasing the demand for immunization services does not automatically translate into providers having the resources necessary to establish or expand their immunization services to meet these growing needs (e.g., personnel, equipment, and technical and/or administrative assistance). 175 In a 2011 study by Freed et al, only 27% of 849 physicians surveyed administered all ACIP-recommended vaccines for adults. Notably, only 12% of respondents indicated that they planned to increase the types of adult vaccines they offered in their practice and 79% did not expect to make any changes.…”
Section: Meeting the Needs For Expanded Access To Immunization Servicesmentioning
confidence: 99%